Integration of Maqāṣid Al-Sharīʿah in the Design of Hybrid Financial Contracts (Uquˉd Murakkabah) - Fattah, Abdul; Anwar, Syahrul (Jurnal Iman dan Spiritualitas, 2025)
This study aims to critically examine how maqāṣid al-sharī‘ah can be systematically integrated into the design, structuring, and evaluation of uqud murakkabah (hybrid contracts) as a core driver of contemporary Islamic financial innovation. Grounded in key concepts such as maqasid, hybrid contracts, maslahah, hilah, and the principles of uṣūl al-fiqh, this research adopts a qualitative library-based methodology, drawing on classical jurisprudence, contemporary scholarship, international Sharia standards, and DSN-MUI fatwas. The scope of analysis includes conceptual foundations, methodological linkages, and practical applications of hybrid contracts in financing, home ownership structures, and sukuk engineering. The findings demonstrate that maqasid integration requires hybrid structures that ensure clarity, transparency, justice, real economic substance, and effective safeguards against hilah and exploitative risk configurations. Key challenges include contractual complexity, limited practitioner awareness of maqasid, and a tendency to mimic conventional financial instruments. Practical recommendations include strengthening maqasid-oriented regulatory frameworks, enhancing the capacity of Sharia Supervisory Boards, and developing measurable evaluation instruments. The study contributes an integrative normative-analytical framework that operationalizes maqasid within hybrid contract design to enhance ethical and welfare-oriented outcomes in Islamic finance. This research introduces a structured maqasid-hybrid contract integration model, offering an actionable evaluative tool for regulators, Sharia boards, and industry practitioners to ensure substantive Sharia compliance beyond formal legality.